2016
DOI: 10.1093/rheumatology/kew298
|View full text |Cite
|
Sign up to set email alerts
|

Survival and organ involvement in patients with limited cutaneous systemic sclerosis and anti-topoisomerase-I antibodies: determined by skin subtype or auto-antibody subtype? A long-term follow-up study

Abstract: LcSSc ATA-positive patients differ from lcSSc ATA-negative patients and dcSSc ATA-positive patients concerning survival and organ involvement. LcSSc patients who are ATA-positive are more likely to develop dcSSc than lcSSc patients who are ATA negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…Mortality was related to both skin and serologic profile (9). Kranenburg et al also demonstrated that lcSSc patients who were positive for anti-topo I antibodies contrasted with lcSSc patients who were negative for anti-topo I antibodies and dcSSc patients who were positive for anti-topo I antibodies in terms of survival and organ involvement (32). Taken together, those studies suggest that subclassification combining antibody profile and skin involvement might predict clinical outcomes more accurately than skin or serologic features alone (9,32).…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was related to both skin and serologic profile (9). Kranenburg et al also demonstrated that lcSSc patients who were positive for anti-topo I antibodies contrasted with lcSSc patients who were negative for anti-topo I antibodies and dcSSc patients who were positive for anti-topo I antibodies in terms of survival and organ involvement (32). Taken together, those studies suggest that subclassification combining antibody profile and skin involvement might predict clinical outcomes more accurately than skin or serologic features alone (9,32).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of ATAs are mainly associated with diffuse cutaneous disease (dcSSc) ( P < 0.0001, OR = 4.26) ( 22 ) and serious organ involvement ( 13 , 24 ). Patients with ATAs had higher SSc-related mortality rate and poor prognosis ( 25 ). ARA presence indicates a high risk of rapidly progressive skin thickening ( P = 0.042, OR = 3.24, 95% CI = 1.44–7.31), and changes in ARA levels may correspond to changes in modified Rodnan skin thickness score ( 26 , 27 ).…”
Section: Classical Disease-specific Autoantibodies In Clinical Manifementioning
confidence: 99%
“…Studies have shown ATA association with a higher probability of interstitial lung disease (ILD) ( P < 0.0001, OR = 4.76, 95% CI = 3.48–6.50), even in ATA-positive patients with lcSSc ( 22 , 25 , 32 ). Recent studies have indicated that ATAs may be related to disability in hand, oral manifestation ( 33 , 34 ), and flexion contractures in metacarpophalangeal and proximal interphalangeal joints ( 35 ), indicating their specificity, to a certain degree, in organ fibrosis.…”
Section: Classical Disease-specific Autoantibodies In Clinical Manifementioning
confidence: 99%
“…By contrast, the dcSSc subset presents a more aggressive progression characterized by severe internal organ manifestations with skin thickening extended proximally to elbows and knees as well as the trunk. In the dcSSc subtype, anti-topoisomerase I autoantibodies (anti-Scl-70) are more frequent, while in the lcSSc subtype, anti-centromere autoantibodies are dominant features (Kranenburg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%